Dra’ Abu el-Naga, Ägypten: Untersuchungen zu Formation und Entwicklung einer oberägyptischen Residenznekropole - Polz, Daniel (e-Forschungsberichte des DAI, 2023)
Following the 2001 discovery of the ruins of a small mud brick pyramid built by King Nub-Kheper-Ra Intef at the end of the 17th dynasty, the area around the pyramid (“area H”) has gradually been identified as paramount for the reconstruction of the development of the Theban Necropolis in general. The excavations at several sub-areas of this location revealed its key position within the necropolis, starting already during Middle Kingdom and lasting well into the Third Intermediate Period.